(Iso‐)form Matters: Differential Implication of Vav3 Variants in Ovarian Cancer. (19th April 2018) - Boesch, Maximilian; Reimer, Daniel; Sopper, Sieghart; Wolf, Dominik; Zeimet, Alain G.
Abstract : This commentary discusses recent results on the role of Vav3 in malignancy, in an effort to begin to define the underlying mechanisms and tissue context by which Vav3 proteins, in particular Vav3.1, promote the progression of malignant diseases and further modulate the response to clinically relevant drugs.